Analysis of Variability in Seed Storage Proteins of Mucuna pruriens var. utilis by using SDS-PAGE - V. VADIVEL; M. PUGALENTHI (Seed Research, 2026)
The influence of agro-ecological conditions of different growing locations on the seed proteins of a tropical under-utilized legume, Mucuna pruriens var. utilis (Wall ex Wight) Baker ex Burck (velvet bean) was investigated. A wide variation was observed in the total seed protein content (22.8-26.1 g/100 g seed flour) and different protein fractions with relation to different growing locations. However, the major seed protein fractions, the albumins and globulins of all the accessions exhibited similar kind of banding pattern and same molecular weight protein sub units when subjected to SDS-PAGE. indicating that the environmental conditions of the growing locations influence only the quantity of the proteins not their molecular characteristics in velvet bean seeds.